Potential antiproliferative and apoptotic effects of pilocarpine combined with TNF alpha in chronic myeloid leukemia cells - CABADAK, HÜLYA; AYDIN OMAY, BANU (My University, 2023)
© 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.Pilocarpine is a selective M1/M3 agonist of muscarinic acetylcholine receptor subtypes. Muscarinic acetylcholine receptors are G protein-coupled receptors. These receptors are different drug targets. The aim of the present work was to investigate the effect of pilocarpine on the expression of M3 muscarinic acetylcholine receptor, the AChE activity, IL-8 release response, and proliferation in K562 cells, via muscarinic receptor activation. Human chronic myeloid leukemic cell cultures were incubated with drugs. Proliferation assays were performed by BrdU assay. Expression of M3 muscarinic acetylcholine receptor and apoptosis proteins such as bcl, bax, cyt C, and caspases was assessed with the semiquantitative Western blotting method. Pilocarpine inhibits chronic myeloid cell proliferation and M3 muscarinic acetylcholine receptor protein expression. Pilocarpine increases caspase-8 and -9 expression levels, upregulating the proapoptotic protein Bax and downregulating the expression levels of the antiapoptotic protein Bcl-2. The apoptotic activity of pilocarpine is associated with an increase in AChE activity. M3 muscarinic acetylcholine receptors can activate multiple signal transduction systems and mediate inhibitory effects on chronic myeloid K562 cell proliferation depending on the presence of 1% FBS conditions. This apoptotic effect of pilocarpine may be due to the concentration of pilocarpine and the increase in AChE level. Our results suggest that inhibition of cell proliferation by inducing apoptosis of pilocarpine in K562 cells may be one of the targets. M3 selective agonist may have therapeutic potential in chronic myeloid leukemia. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Pharmacology; Cholinergic receptors; Leukemia cells; M3 muscarinic receptor agonist; TNFα